HUBUNGAN AKTIVITAS FISIK TERHADAP PREVALENSI SIMPTOM DEMENSIA PADA CALON JEMAAH HAJI LANSIA DI KBIH KODAM I BUKIT BARISAN KOTA MEDAN TAHUN 2020 - JELITA FORTUNA; ELMAN BOY (JURNAL ILMIAH KOHESI, 2021)
Lifestyle and especially physical activity are the main focus for someone who is elderly, physical activity can provide valueand a positive effect on improving cognitive, physical, mental, and social functions. Decreased cognitive function is a majorconcern for the elderly, lower cognitive function can cause several risks such as: death, disability, poor quality of life,dementia and several other neurodegenerative diseases. To find out the relationship between activities and dementiasymptom events in elderly Hajj Candidates at KBIH Kodam I Bukit Barisan Medan City in 2020. Correlative analytic researchwith cross sectional design. Sampling by purposive sampling. Data collection by interviewing the IPAQ and MMSEquestionnaires. The results of the analysis test using the Chi Square test were found to be p value 0,001 (p <0.05) and thePearson correlation test was found to be r value of 0.780. There is a significant relationship between physical activity and theprevalence of dementia symptoms in prospective elderly pilgrims at KBIH Kodam I, Bukit Barisan, Medan City in 2020.